The Stiffness‐Sensitive Transcriptome of Human Tendon Stromal Cells. Issue 7 (20th January 2023) - Hussien, Amro A.; Niederoest, Barbara; Bollhalder, Maja; Goedecke, Nils; Snedeker, Jess G.
Abstract: Extracellular matrix stiffness is a major regulator of cellular states. Stiffness‐sensing investigations are typically performed using cells that have acquired "mechanical memory" through prolonged conditioning in rigid environments, e.g., tissue culture plastic (TCP). This potentially masks the full extent of the matrix stiffness‐driven mechanosensing programs. Here, a biomaterial composed of 2D mechanovariant silicone substrates with simplified and scalable surface biofunctionalization chemistry is developed to facilitate large‐scale cell culture expansion processes. Using RNA sequencing, stiffness‐mediated mechano‐responses of human tendon‐derived stromal cells are broadly mapped. Matrix elasticity ( E .) approximating tendon microscale stiffness range ( E . ≈ 35 kPa) distinctly favors transcriptional programs related to chromatin remodeling and Hippo signaling; whereas compliant stiffnesses ( E . ≈ 2 kPa) are enriched in processes related to cell stemness, synapse assembly, and angiogenesis. While tendon stromal cells undergo dramatic phenotypic drift on conventional TCP, mechanovariant substrates abrogate this activation with tenogenic stiffnesses inducing a transcriptional program that strongly correlates with established tendon tissue‐specific expression signature. Computational inference predicts that AKT1 and ERK1/2 are major stiffness‐sensing signaling hubs. Together, these findings highlight how matrix biophysical cues may dictate the transcriptional identity of tendon cells, and how matrix mechano‐reciprocity regulates diverse sets of previously underappreciated mechanosensitive processes in tendon fibroblasts. Abstract : Extracellular matrix stiffness‐sensing studies are typically carried out using cells that have acquired "mechanical memory" through progressive passaging in rigid mechanical environments, e.g., tissue culture plastic (TCP). This confounds the mechanistic experiments that investigate matrix stiffness‐driven mechanosensing programs. This work reports the formulation of a mechanovariant silicone‐based platform with tunable elasticity and tendon‐like elastic ( E .) moduli, and with optimized chemistry to make it amenable to large‐scale cell expansion practices.